Analyzing User Satisfaction of the SMP Negeri 1 Sungai Lilin Website Using the End User Computing Satisfaction (EUCS) Method - Nurhalimah, Siti; Ratnasari, Asti; Rochmadi, Tri; Wicaksono, Yanuar (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Education plays a central role in society, with schools serving as crucial institutions in providing access to relevant information for all stakeholders. With advancements in technology, many schools have established an online presence through their websites. SMP Negeri 1 Sungai Lilin is one such school that provides various information related to school activities on its website. However, overall user engagement and feedback, particularly from students, have been limited, and the level of user satisfaction remains unknown. This study aims to analyze the user satisfaction of the school website using a quantitative descriptive approach to test specific hypotheses. Data were collected from 250 respondents selected through purposive sampling, conducted at SMP Negeri 1 Sungai Lilin between February and April 2024. The End User Computing Satisfaction (EUCS) method was employed to assess user satisfaction and the influencing factors. EUCS evaluates satisfaction based on five parameters: content, accuracy, format, ease of use, and timeliness. Data analysis was conducted using multiple linear regression and classical assumption tests, processed with SPSS version 23. Initial validity and reliability tests revealed inadequacies, but subsequent tests confirmed that all instruments were valid and reliable. The results confirm that all research hypotheses are accepted. The F-test results indicate that the regression coefficients of content, accuracy, format, ease of use, and timeliness significantly affect user satisfaction (sig < 0.05). The T-test results further reveal that each variable positively influences user satisfaction individually (sig < 0.05). An R Square value of 0.297 suggests that 29.7% of user satisfaction is explained by the variables of content, accuracy, format, ease of use, and timeliness, indicating a weak relationship, while the remaining 70.3% is influenced by other factors not included in this study. The findings indicate that respondents generally exhibit low levels of satisfaction when using the SMP Negeri 1 Sungai Lilin website, as evidenced by the influence of content, accuracy, format, ease of use, and timeliness on user satisfaction.